Effect of Protean Career Attitudes on Organizational Commitment of Employees with Moderating Role of Organizational Career Management - Khan, Muhammad Latif; Salleh, Rohani; Bin Hemdi, Mohamad Abdullah (International Review of Management and Marketing, 2016)
The purpose of this study is to develop a conceptual framework for theoretical background explaining about the expected relationship between protean career attitudes and organizational commitment with moderating role of organizational career management within today’s unstable and uncertain career scenario. Career literature shows that individuals having a protean career attitudes are less committed to their organizations however any practical researches on this relationship are not sufficient and need further empirical investigation. Review literature summarize the organizational commitment and it possible relationship with protean career attitudes with moderating role of organizational career management. This is followed by conceptual framework and propositions. Further It is suggested that individuals with protean career attitudes do not results in less organizational commitment until organization does not ignore them for organizational career management. Upcoming future research must examine practically the correlation between protean career attitudes and organizational commitment of employees with moderating role of organizational career management. HR practitioners, managers, and organizations should develop the protean career attitudes in order to utilize their valuable skills and abilities. It is also suggested that organization can enhance the organizational commitment of employees when they perceive sufficient career development opportunities. This paper contributes to the career literature by theoretically identifying the relationship between protean career and organizational commitment with moderating impact of organizational career management. In future this study will empirically investigate the correlation between protean career attitudes and organizational commitment with moderating role of organizational commitment of hotels managers in Malaysia. Keywords: Protean Career Attitudes, Organizational Commitment, Organizational Career Management JEL Classification: L2